Treatment Preferences in Young Adults with Moderate to Severe Psoriasis: A Qualitative Study from the Nordic Countries - Flora Nicol Balieva; Louise Catton; Birgitta W. Claréus; Kjersti Danielsen; Frederik Fierens; Lars Iversen; Leena Koulu; Amra Osmanecevic; Rafael Pasternack; Lone Skov (Adis, Springer Healthcare, 2023)
Abstract Introduction The purpose of this study is to explore treatment preferences and identify patient characteristics in young bio-naive adults with moderate to severe psoriasis in the Nordic countries (Norway, Finland, Sweden, and Denmark). Methods Patients were 18-45 years old and bio-naive but referred for biologic treatment of moderate to severe psoriasis. Patients were included at eight Nordic dermatology clinics. Patients with significant comorbidity or psoriatic arthritis were excluded. The Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) were assessed along with basic patient information. A semistructured interview guide was used in individual qualitative interviews, asking patients about their treatment preferences and reasons, disease journey, and disease management. The interviews were analyzed using thematic content analysis. Twenty-four patients sufficed to reach saturation in this qualitative study. Results The patient sample characteristics represented a qualitative variation in age, sex, symptoms, duration of disease, and country. We included a total of 12 male and 12 female patients. The mean age was 34 years (range 18-45 years), the mean age at diagnosis was 20 years (range 6-34 years), the mean ± standard deviation (SD) time since diagnosis was 13 ± 8 years, PASI was 9.5 ± 4.7, and DLQI was 15.2 ± 6.4. Interviews suggested that both the burden of disease as well as the burden of treatment influenced patient preferences regarding treatment attributes, hence getting alleviation from symptoms did not alone influence patient preferences. Time, effort, and inconvenience related to psoriasis treatments also influenced patient preferences. Conclusions This first in-depth, qualitative study in young bio-naive adults with psoriasis suggests that patient preferences are focusing not only on symptom relief but also on alleviating the burden of psoriasis treatment. Understanding the reasons for patient preferences and the perspectives of young adults is needed to guide individual shared decision-making in psoriasis management.